Star-gazing Cowboys - Jim Hoy (Symphony in the Flint Hills, 2019)
Introduction: When the Great American Cowboy first emerged from the dust of the Old Chisholm Trail, he most likely used the sky as his timepiece; pocket watches would have been an expensive luxury for most of these hired men on horseback.